Chili Plants: Nutrition Content and Local Varieties as a Genetic Resources - Makhziah; Tri Mujoko; Sukartiningrum (Future Science, 2020)
Chili (Capsicum sp.) is a vegetable commodity that is widely grown throughout the world after tomatoes are a member of the Solanaceae family, which have very many types, ranging from not spicy to very spicy. Chili originates from South America and Central America, Peru and Mexico and then brought by the Portuguese to Europe and Asia then spread throughout the world. Chili contains many compounds that are good for health, vitamin C, vitamin A, vitamin E, folic acid, flavonoid, phenol, capsaicin which can be used to treat malnutrition in society and non-infectious diseases such as heart disease, diabetes, cancer. The content of the nutrition depends on the genotype, environmental conditions, and the fruit ripening phase at harvest. In Indonesia, there are many local varieties or landraces of chili that have adapted well to the local environment. Local varieties are good genetic resources for developing new superior varieties of chili that have the quantity, quality, and resistance to environmental stress.